Impact of a public awareness campaign on out-of-hospital cardiac arrest incidence and mortality rates - Nehme, Z.; Andrew, E.; Bernard, S.; Patsamanis, H.; Cameron, P.; Bray, Janet; Meredith, I.; Smith, K. (Oxford University Press, 2017)
Aims: Increased public awareness of the warning signs of a heart attack and the importance of early medical intervention may help to prevent premature deaths from out-of-hospital cardiac arrest (OHCA). We sought to investigate the impact of the Heart Foundation's public awareness campaigns on the monthly incidence of, and deaths from, OHCA in Melbourne, Australia. Methods and results: Between July 2005 and June 2015, we included registry data for 25 060 OHCA of presumed cardiac aetiology. Time series models with distributed lags were used to explore the effect of campaign activity on OHCA outcomes. A sensitivity analysis involving segmented regression of the pre-intervention, intervention, and post-intervention time segments was also performed. The mean monthly incidence of, and deaths from, OHCA was 207 and 189 events respectively. After adjustment for temporal trends, campaign activity was associated with a 6.0% [95% confidence interval (CI): 2.8-9.0%; P < 0.001] reduction in the monthly incidence of OHCA, or 11.7% (95% CI: 7.7- 15.5%, P< 0.001) with the addition of residual effects in two additional lag months. Similarly, the rate of deaths from OHCA reduced by 6.4% (95% CI: 2.8-10.0%; P1/40.001) during months with campaign activity. Campaign activity had a greater effect in males and patients aged-65 years, and reduced the incidence of OHCA in unwitnessed and initial non-shockable arrests. In the segmented regression analysis, the intervention period was associated with a 15.2% (95% CI: 9.2-20.9%; P < 0.001) reduction in the mean monthly incidence and a 16.6% (95% CI: 9.9-22.7%; P < 0.001) reduction in deaths from OHCA. Conclusion: A comprehensive mass media campaign targeting the community's awareness of heart attack symptoms was associated with a substantial reduction in the incidence of OHCA and associated deaths.